Necrosis of intact premolar caused by an adjacent apical infection: a case report - Saeed Asgary; Laleh Alim Marvasti (Korean Academy of Conservative Dentistry, 2013)
Although periapical inflammatory lesions are usually resulted by infection in the root canal system, this rare case showed that a periapical lesion related to an infected tooth may cause pulpal necrosis in adjacent intact tooth, with no history or clinical signs of caries, disease, trauma or developmental anomaly. This case also suggests that the periapical lesion can be treated conservatively, without surgical intervention. Furthermore, this case highlights the importance of prompt treatment of apical periodontitis before the lesion becomes extensive as well as follows up of large lesions.